The use of electrical flocculation for the recovery of microalga, chlorella vulgaris - Audrey Rose, Andrew (Universiti Malaysia Sarawak (UNIMAS), 2010)
Chlorella vulgaris has been one of the preferred microalgal species in algal biofuel production. In the present study, this alga was grown in batch and outdoor mass cultures under varying concentration of fertilizer and growth promoter in NGP medium. The biomass of the C. vulgaris in the outdoor cultivation was harvested using an electrical flocculation method with the addition of chitosan. Results showed that the flocculation efficiency of this microalga increased when higher concentration of chitosan (3g/L) used and higher voltage (1 OV) applied. The obtained biomass was later extracted for its lipid content. Lipid analysis showed that the lipid content in the microalga using current mass cultivation method was low, about 2.17% of dry weight.